Dynamic Model of a Robotic Manipulator with One Degree of Freedom with Friction Component - Jose A. G. Luz Junior; Jose M. Balthazar; Mauricio A. Ribeiro; Frederic C. Janzen; Angelo Marcelo Tusset (International Journal of Robotics and Control Systems, 2023)
This research aims to develop a dynamic model of a robotic manipulator with one degree of freedom by incorporating the LuGre friction model. The study combines a mathematical model with experimental data analysis, using the Stribeck curve and Non-linear Least Square method for Parameter Identification. The purpose of the study is to improve the accuracy of the model and enhance the performance of robotic manipulators. The LuGre model is chosen for its ability to capture the nonlinear behavior of friction, which is a significant source of error in robot control systems. The effectiveness of the proposed representation is evaluated by comparing the simulation results of the dynamic model with experimental data obtained from a prototype. The results indicate that the model accurately captures the nonlinear behavior of friction, and the proposed approach can be used to develop more accurate models for control purposes.